Updated description of the Dicynodontipus- and Chirotherium-bearing slab from the Solling Formation, Hildburghausen Town, Germany - de Valais, Silvina (2020)
Fil: de Valais, Silvina. Universidad Nacional de Río Negro. Instituto de Investigación en Paleobiología y Geología. Río Negro, Argentina.